Dengue Fever Presenting as Acute Pancreatitis - Seetharam, Prasad (Eurasian J Med, 2010)
A 56-year-old non-alcoholic male was admitted with complaints of severe abdominal pain and was diagnosed with acute pancreatitis after blood investigations and a computed tomography scan of the abdomen. He developed a high-grade fever on the third day of admission, and serology tested positive for dengue. Treatment for dengue was instituted, leading to a good response and complete resolution of pancreatitis. The patient has been doing well and has had no recurrence of pancreatitis at the end of one year of follow-up.